2020
DOI: 10.28989/senatik.v6i0.420
|View full text |Cite
|
Sign up to set email alerts
|

Perancangan Simulasi Turbin Angin Sumbu Horizontal (TASH) Dengan Variasi Jumlah Blade Dan Variasi Sudut Pitch Menggunakan Aplikasi Q-Blade

Abstract: Turbin angin memanfaatkan energi kinetik dari angin dan kemudian mengkonversinya menjadi energi listrik. Ada dua tipe turbin angin yaitu Turbin Angin dengan Sumbu Horizontal (TASH) dan Turbin Angin dengan Sumbu Vertical (TASV). Turbin Angin Sumbu Horisontal adalah jenis turbin angin dimana sumbu rotasi turbin nya diorientasikan secara sejajar dengan arah angin agar menghasilkan power. Sedangkan Turbin Angin Sumbu Vertikal adalah jenis turbin angin dimana sumbu rotasi turbin ini tegak lurus dengan arah angin at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…Arga Gideon Sarwando, Untung Budiarto, Ahmad Fauzan Zakki conducted research on the analysis of the effectiveness of horizontal axis wind turbines with variations in the number and type of airfoils as a source of additional electrical energy in fisheries inspections. It was found that the NACA 0018 airfoil type had the highest of the NACA 0015 and NACA 0025, with a torque of 351.72 Nm, a power of 11.05 KW, and a power coefficient of 0.488 [10]. In research on horizontal axis wind turbine (HAWT) blades with a power output of 10,000 Watts using blade element momentum (BEM) theory and a modified stall model, and blade aerodynamics were simulated to determine the flow structure and aerodynamic characteristics [11].…”
Section: Review Of Literaturementioning
confidence: 99%
“…Arga Gideon Sarwando, Untung Budiarto, Ahmad Fauzan Zakki conducted research on the analysis of the effectiveness of horizontal axis wind turbines with variations in the number and type of airfoils as a source of additional electrical energy in fisheries inspections. It was found that the NACA 0018 airfoil type had the highest of the NACA 0015 and NACA 0025, with a torque of 351.72 Nm, a power of 11.05 KW, and a power coefficient of 0.488 [10]. In research on horizontal axis wind turbine (HAWT) blades with a power output of 10,000 Watts using blade element momentum (BEM) theory and a modified stall model, and blade aerodynamics were simulated to determine the flow structure and aerodynamic characteristics [11].…”
Section: Review Of Literaturementioning
confidence: 99%
“…Pada kecepatan angin relatif rendah, performa turbin savonius dengan jumlah 2 sudu memiliki efisiensi lebih rendah dari pada jumlah 3 dan 4 sudu [13]. Turbin dengan putaran besar tidak efektif digunakan di daerah dengan kecepatan angin yang rendah karena daya yang dihasilkan tidak dapat terpenuhi dari putaran turbin [14]. Parameter seperti sudut serang (angle of attack), sudut sudu/puntir (twist angle), tip speed ratio (TSR) dan lebar sudu (chord length) dapat mempengaruhi efisiensi turbin angin.…”
Section: Pendahuluanunclassified